Multi-wavelength source based on SOA and EDFA in a ring cavity resonator - Harun, Sulaiman Wadi; Shahi, Sharifeh; Sulaiman, Abdul Hadi; Ahmad, Harith (INOE, 2008)
A multi-wavelength source incorporating a Semiconductor Optical Amplifer (SOA) and a Erbium-doped fiber amplifier (EDFA) in a ring cavity configuration is demonstrated. The multi wavelength source is able to generate more than 12 channels at -35 dBm and above with a channel spacing of 0.8 nm at a SOA bias current of 350 mA and 980nm pump power of 92 mW. The number of wavelengths generated can be controlled by adjusting the SOA bias current and the birefringence of the ring cavity using the Polarization Controllers (PCs). The proposed laser has a channel spacing suitable for DWDM and sensing applications and shows stable operation at room temperature.